Determinan Perencanaan Pembangunan Manusia Di Pulau Jawa - Nur, Indrayansyah; Sukarno, Sukarno; Sopian, Sopian (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The quality of human resources has an important contribution to the success of development in the context of increasing people's welfare. This research aims to identify the factors that make a major contribution to the increase in the HDI and examine the effect of poverty and unemployment on the achievement of quality human resource development. By using secondary data sources sourced from the Central Bureau of Statistics and the Directorate General of Fiscal Balance as well as the EViews analysis tool, the research results show that life expectancy, expected length of schooling, average length of schooling, spending per capita have a significant effect on the development of the quality of human resources on the island of Java. Meanwhile, poverty and unemployment have a negative impact on the development of the quality of human resources on the island of Java. The results of this research might be become a foundation for policy makers to explore education spending and health spending instruments to improve the quality of human resources. The results of the research also show that quality human resources are able to improve people's welfare through economic development, reducing poverty and unemployment. Keywords: Human development; economic development; education; health; poverty; unemployment